2015
DOI: 10.1007/s11356-015-5669-y
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in surface sediments of the Taiwan Strait: geochemical characteristics and environmental indication

Abstract: The concentration and geochemical fractionation of six trace metals related with environmental quality assessment, namely Cd, Cr, Cu, Ni, Pb, and Zn, in 30 surface sediments from both inshore and offshore areas of the Taiwan Strait were measured to investigate their distribution characteristics, evaluate their potential mobility, and assess their pollution status. The geoaccumulation index results indicated that, on average, the studied metals presented an order of Cd>Pb>Ni>Zn>Cu>Cr and were practically in unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Table 2 also shows the metal values of other coastal areas in China. The average concentrations of the studied metals in this study were comparable to the values reported for the surface sediments of the Taiwan Strait (Gao et al, 2016), Xiamen bay (Lin et al, 2014), and Laizhou Bay (Zhuang and Gao, 2014) (Table 2). The metal concentrations in this study were apparently lower than the values reported for the Jinzhou Bay (Li et al, 2012), which is one of the most heavily polluted coastal region in China (Gao et al, 2014;Gao et al, 2016).…”
Section: Spatial and Seasonal Variations Of Total Metal Concentration...supporting
confidence: 87%
See 1 more Smart Citation
“…Table 2 also shows the metal values of other coastal areas in China. The average concentrations of the studied metals in this study were comparable to the values reported for the surface sediments of the Taiwan Strait (Gao et al, 2016), Xiamen bay (Lin et al, 2014), and Laizhou Bay (Zhuang and Gao, 2014) (Table 2). The metal concentrations in this study were apparently lower than the values reported for the Jinzhou Bay (Li et al, 2012), which is one of the most heavily polluted coastal region in China (Gao et al, 2014;Gao et al, 2016).…”
Section: Spatial and Seasonal Variations Of Total Metal Concentration...supporting
confidence: 87%
“…The former assessment methods of sediment metal contamination are based on the total concentrations of metals. In addition to the total concentrations, the geochemical composition of metals is equally important to determine their potential toxicity and threat to ecosystems (Sahuquillo et al, 2003;Gao et al, 2016). According to the study of Perin et al (1985), the acid soluble fraction (F1) of metal with no more than 1% of its total concentration is considered to have no risk to the environment; the percentage of metal in this fraction falling in the range of 1-10% indicates a low risk to the environment; its falling in the range of 10-30% indicates a medium risk to the environment; its falling in the range of 30-50% indicates a high risk to the environment; and the percentage higher than 50% indicates a very high risk to the environment.…”
Section: Assessment Methods Of Metal Contaminationmentioning
confidence: 99%
“…It is commonly found that the fractions of trace metals in marine sediment analyzed by the Tessier's sequential extraction method generally follow the order: residual (F5) > Fe-Mn oxides (F3) > organic (F4) > carbonate (F2) > exchangeable (F1), except Mn and Pb [27,39,42,[49][50][51][52][53]. However, the organic fraction of Cu frequently ranks as the second important fraction and contributes a significant portion of the total concentrations in some marine environments [27,28,41,49,54].…”
Section: Trace Metals Speciationmentioning
confidence: 99%